The world and its shades of green: a meta‐analysis on trophic cascades across temperature and precipitation gradients. Issue 1 (16th October 2012) - Rodríguez‐Castañeda, G.; Sykes, Martin
Abstract Aim To assess effects of current global temperature and precipitation gradients on the trophic function of plant–herbivore–predator interactions. Specifically, I study effects of climatic gradients on factors that control herbivore abundances: top‐down, bottom‐up trophic cascades and plant defences. I include predictions of climate change on shifts in trophic function, under the assumption that temperature and precipitation affect the physiology and performance of plants, herbivores and predators. Location Global. Methods A search of the relevant experiments on trophic interactions was conducted using the Web of Science and Scielo databases. Strength of trophic interactions from each experiment was studied by the calculation of the log ratio effect size (Ln R) of the control and experimental means. Each study was georeferenced and mean annual temperature (MAT) and total annual precipitation (TAP) were determined for each study location. Effect size of trophic interaction studies across the world were correlated with these environmental variables. Results In total, 387 effect sizes were extracted from the literature. With the exception of bottom‐up trophic cascades, trophic interactions and factors controlling herbivore abundance exhibited significant linear or quadratic relationships with either temperature or precipitation gradients: plant growth, predation and the effect of plant defence on herbivores increased with temperature. In contrast, plant growth and herbivory increased with precipitation across ecosystems. Finally, top‐down trophic cascades increased towards the extremes of MAT and TAP gradients. Main conclusions This study shows climatic gradients not only affect species geographic distributions and physiological tolerance but also the strength of their trophic functionality. This is especially true for the main biotic controls of herbivore populations (i.e. predation, top‐down trophic cascades and plant defences). These results suggest future climate change will cause shifts in the strength of trophic interactions, resulting in increased or reduced population control of herbivores across global ecosystems.